Modern Applied Economics / A Problem - Oriented Approach to Economic Theory - Heather Ken (Harvester Wheatsheaf, 1994)
A major textbook that teaches the foundations of economic theory and concepts in the context of applied, real-world problems. Preface, Acknowledgements, Eastern European Economic Reforms: The Road to Freedom?, The Stock Market: A Quick Way to Riches?, Traffic Jams: Could Britain Import a Solution from Singapore?, The National Health Service: is Radical Treatment Needed?, The Regional Problem: Why is it so Depressing?, Small Firms: on Being Small and Beautiful, British Coal: Why the Future is Black, Europe's Airline Prices: The Sky's the Limit?, Business Behavior: Are Profits Everything?, Government Spending: Do we Get Value for Money?, Trade Unions: Labor Market Manipulators?, Damaging the Earth: How Much Does it Really Matter?, Unemployment: What Can the Government Do?, Does Britain Invest Enough, Beating Inflation: Is It Really Worth It, Privatization: A Supply Side Improvement?, Does the UK Want an Independent Central Bank?, Giving Up Sterling: Too High a Price to Pay?, Appendices, Index.